2012
DOI: 10.1016/j.jvs.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of duplex-detected stenosis after femoropopliteal endovascular therapy suggests questionable clinical utility of routine duplex surveillance

Abstract: DUS does not reliably predict arterial occlusion after EVT. Stenosis after EVT appears to have a different natural history than restenosis after vein graft bypass. EVT patients are more likely to have severe stenosis when they present with recurrent symptoms, in contrast to vein graft patients, who commonly have occluded grafts when they present with recurrent symptoms. The potential impact of routine DU-directed reintervention in patients after EVT is questionable. The natural history of DU-detected stenosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…Though Mills et al [11] recommended anticoagulation therapy for the treatment of failing grafts, many other authors recommended an earlier treatment of the target lesion with endovascular or surgical intervention [6,18]. Various procedures have been used to treat failing grafts including EVT (e.g., PTA, cutting balloon angioplasty, cryoplasty or stenting) and OSR (e.g., vein patch angioplasty, proximal or distal vein graft extension).…”
Section: Discussionmentioning
confidence: 99%
“…Though Mills et al [11] recommended anticoagulation therapy for the treatment of failing grafts, many other authors recommended an earlier treatment of the target lesion with endovascular or surgical intervention [6,18]. Various procedures have been used to treat failing grafts including EVT (e.g., PTA, cutting balloon angioplasty, cryoplasty or stenting) and OSR (e.g., vein patch angioplasty, proximal or distal vein graft extension).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high sensitivity and specificity of the echo Doppler in the follow‐up of the infrainguinal vein grafts, there is conflicting information regarding the benefit in terms of cost‐effectiveness and salvation of the extremity . In addition, tracking through echo Doppler has not shown to increase the permeability of the prosthetic grafts nor of the endovascular techniques, and therefore, on the basis of the results obtained in this study and the demonstrated efficiency of the new wireless methods of clinical assistance, the establishment of a new surveillance protocol for the procedures in vascular surgery based on WSN technology could be of interest in the future.…”
Section: Discussionmentioning
confidence: 88%
“…Por último, se ha demostrado la efectividad del eco-doppler en el postoperatorio inmediato de una técnica endovascular (166) para el diagnóstico de estenosis residuales, sin embargo, otros estudios han demostrado que no predice con exactitud el fracaso de estas técnicas durante el seguimiento (167) . No obstante, no existen ensayos clínicos randomizados que recomienden el seguimiento de los procedimientos endovasculares mediante eco-doppler.…”
Section: Protocolos De Seguimiento En Cirugía Vascularunclassified